1999
DOI: 10.1126/science.286.5440.771
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Regulation of TGF-β Signaling by the SnoN Oncoprotein

Abstract: y g by addition of nonrecombinant pCDNA3, as necessary. Results represent three t o six different transfected cultures, with the experiments performed on at least two different days. For dark conditions, plates of NIH 313 cells were wrapped in foil immediately after transfection until the time of harvesting (48 hours), except for a single brief medium change performed under dim red light (Kodak Safelight, Wratten Series 1A) 24 hours before harvesting. 18. E. A. Griffin Jr., D. Staknis, C. J. Weitz, unpublished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
460
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(492 citation statements)
references
References 42 publications
(15 reference statements)
19
460
0
6
Order By: Relevance
“…Much of the function of Smads is either mediated or modulated through association with a number of other transcription factors such as junB, ATF-3, and SnoN, whose expression may also be regulated by TGF-b (Jonk et al, 1998;Stroschein et al, 1999;Kang et al, 2003). In line with those observations, TGF-b controls the expression of Cited2, as demonstrated in MDA-MB-231 and MCF-10A cells (Chen et al, 2001).…”
Section: Cited2 Is a Co-activator For Smad3mentioning
confidence: 61%
See 1 more Smart Citation
“…Much of the function of Smads is either mediated or modulated through association with a number of other transcription factors such as junB, ATF-3, and SnoN, whose expression may also be regulated by TGF-b (Jonk et al, 1998;Stroschein et al, 1999;Kang et al, 2003). In line with those observations, TGF-b controls the expression of Cited2, as demonstrated in MDA-MB-231 and MCF-10A cells (Chen et al, 2001).…”
Section: Cited2 Is a Co-activator For Smad3mentioning
confidence: 61%
“…SnoN, a Smad-binding repressor, is rapidly degraded in response to TGF-b. At later stages of TGF-b stimulation, TGF-b induces SnoN expression, resulting in termination of Smad-mediated transactivation (Stroschein et al, 1999;Sun et al, 1999). Smad7, an antagonistic Smad induced by TGF-b, interferes with the binding between Smad2/3 and TGF-b receptor, to attenuate TGF-b-mediated responses (Hayashi et al, 1997).…”
Section: Cited2 Is a Transcriptional Modulator In Tgf-b Signaling Patmentioning
confidence: 99%
“…SnoN is a transcriptional co-repressor that interacts with Smad2/3 and Smad4, and represses TGF-β signalling through recruitment of HDAC (histone deacetylase) to Smads [40][41][42]. Bonni et al [21] have reported that Smurf2 associates with SnoN via Smad2, and induces ubiquitin-mediated degradation of SnoN, but not that of Smad2.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy suggests that additional genetic insults may also contribute to the HPE phenotype associated with patients bearing Tgif mutations, whereas the loss of TGIF function in mice may be compensated for by other TGF-␤ antagonists. Two such kinds of antagonists are C-Ski and SnoN, two structurally related TGF-␤ antagonists (Stroschein et al, 1999;Wu et al, 2002). Similar to TGIF, C-Ski and SnoN proteins suppress TGF-␤ signaling by interacting with Smad proteins, recruiting histone deacetylase complex and competing out transcriptional activators (reviewed by Liu et al, 2001).…”
Section: Tgif ؊/؊ Embryos Show Normal Brain and Spinal Cord Patterningmentioning
confidence: 99%